KETERLIBATAN KYAI SEBAGAI PESERTA PILKADA PAMEKASAN TAHUN 2018 - Bustanol Husein, Mohammad (Universitas Madura, 2018)
On Local Leader’s election 2018, KyaiIn Pamekasan would be a centre of fascination political interest and absolutely about political support. Special Moment, in this political season happened a competition head-to head betwen Kyai whose simmiliariy party background. This moment never came on local leader’s election since ORBA era. This research focus on reason of involvment of kyai as participants in local leader.s election. This theory used Pareto’s Theory of elite and used concept of political kyai involvement. This research chose qualitative approach and used Snow Ball Sampling to get a deep interviewess. The Result, First, The reason of Political Kyai Involvement as participant on local leader’s election based on awareness of Kyai to take prophetic role. Therefore, Kyaimust take action to solve problem of people. Secondly, Involvement of Kyai had influenced politic and social conditon (oppurtunity analysis and benefit) who make himself think hard to calculate.